Restricted immunoglobulin constant heavy G chain genes in primary immunodeficiencies - Oxelius, Vivi-Anne (Clinical immunology (Orlando, Fla.), 2008)
Some primary immunodeficiencies (PIDs) express low serum levels of antibodies. The constant heavy G chain (IGHG) genes, also representing Fc domains of gamma 3, gamma 1 and gamma 2 on chromosome 14q32.3, genotyped by the alternative IgG subclass allotypes, found in four fixed IGHG haplotypes, designating four B cell variants, were identified by a competitive ELISA and double immunodiffusion. IGHG genes were hypothesized to contribute to the development of PIDs. From 235 Caucasian patients, the homozygous IGHG *bf-n/*bf-n diplotype (B*(bf-n)/B*(bf-n) cells) dominated significantly in 43 IgG2 deficiency (OR 6.0), 32 common variable immunodeficiency (OR 4.6) and 22 Ataxia telangiectasia (OR 3.0) and the IGHG*ga-n/*ga-n diplotype (B*(ga-n)/B*(ga-n) cells) dominated in 53 IgG3 deficiency (OR 10.6) and 21 Wiscott-Aldrich syndrome (OR 4.1). 62 IgA deficiency patients were dominated by both diplotypes (OR 2.3 and OR 2.8 respectively). Restricted IGHG genes, restricted IgG allotypes (Fc domains) and restricted B cells are significant in PIDs for diagnosis, treatment and pathogenetic mechanisms